Soil phosphorus composition, loss risk and contribution to the aquatic environment in a typical agricultural area - Tianhai Ma (IWA Publishing, 2021)
River eutrophication risk increased significantly in agricultural areas. In this paper, spatial variability of soil phosphorus (P) and loss risk in the Jialu River Basin, China, were analyzed using a geostatistical approach. The correlation between soil and river sediment P was analyzed to identify the main aquatic P source. The results showed that inorganic phosphorus (IP) was the main form of soil TP (82.13%), but the ratio of apatite phosphorus (AP) and non-apatite phosphorus (NAIP) varied between different soil types. AP was the primary form of IP in fluvo-aquic cinnamon soil, while NAIP dominated in meadow aeolian sandy soil. Calculated soil total dissolvable P (TDP, 94–622 mg/kg) exceeded the environmental threshold. High TDP (>400 mg/kg) in mixed soil and sandy soil indicated a high P loss risk. The spatial variability of soil P was moderate to weak, indicating a low heterogeneity. In sediment, IP and AP showed a significant correlation with total organic carbon (p < 0.05), indicating a P source of soil erosion. Sediment AP had a significant positive correlation with soil AP (p < 0.05), confirming soil as the main source of sediment P. Furthermore, an accumulation of sediment P along the Jialu River and its consistency with water TP was revealed. HIGHLIGHTS Based on a geostatistical approach, spatial variability of soil P and loss risk in Jialu River Basin, China, were analyzed.; IP is the main form of soil TP in the Jialu River Basin and high TDP in mixed soil and sandy soil indicated a high P loss risk.; The correlation between soil and river sediment P showed that soil is the main source of sediment P.;